2006
DOI: 10.1002/ca.20402
|View full text |Cite
|
Sign up to set email alerts
|

Musculocutaneous nerve: Histotopographic study and clinical implications

Abstract: Surgical reconstruction of severe brachial plexus injuries includes nerve grafting and neurotization techniques of the musculocutaneous nerve (MCN) to recover elbow flexion. In treating recurrent anterior shoulder instability, knowledge of the topography of the MCN is important for the margin of safety available during dissection. The present study evaluates the origin and course of the MCN and its branches, and their relationships to bone landmarks. Twelve unembalmed cadavers (50-82 years old) were dissected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Helfet (1958) recognized the clinical significance of a high entry of the MCN into coracobrachialis. Subsequently, several investigators have suggested that the entry point of the MCN into coracobrachialis is clinically important, with a correlation between high entry points and frequency of nerve injuries being reported (Flatow et al, 1989;Ozturk et al, 2005;Macchi et al, 2007). Some studies have reported cases in which the MCN does not pierce cor-acobrachialis, in which case a direct branch from lateral cord of the brachial plexus was observed to supply the muscle (Eglseder and Goldman, 1997;Venieratos and Anagnostopoulou, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Helfet (1958) recognized the clinical significance of a high entry of the MCN into coracobrachialis. Subsequently, several investigators have suggested that the entry point of the MCN into coracobrachialis is clinically important, with a correlation between high entry points and frequency of nerve injuries being reported (Flatow et al, 1989;Ozturk et al, 2005;Macchi et al, 2007). Some studies have reported cases in which the MCN does not pierce cor-acobrachialis, in which case a direct branch from lateral cord of the brachial plexus was observed to supply the muscle (Eglseder and Goldman, 1997;Venieratos and Anagnostopoulou, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Retroperitoneal pelvic connective tissue may act as a shock absorber, particularly efficient in response to sudden increases in abdominal pressure [De Caro et al, 1998]. The arrangement of the fibroadipose tissue sheaths of the epineurium of the musculocutaneous nerve may be compared to a 'telescope', which allows harmonic compliance between variations in the length of the coracobrachialis muscle with respect to the constant course of the musculocutaneous nerve [Macchi et al, 2007]. The deep fibroadipose connective layer of the SMAS may represent a buffer device with respect to deep muscle activity, since it can modulate excessive involvement of facial physiognomy due to the direct transmission of collateral contraction effects during the activity of the masseter and buccinator muscles (masticatory and phoniatric functions) to the overlying cutaneous facial plane.…”
Section: Discussionmentioning
confidence: 99%
“…For each region of the subcutaneous tissue, the following parameters were recorded: mean thickness of the subcutaneous tissue, superficial and deep fibroadipose connective tissue, superficial fascia and septa. The mean area and circularity factor of adipose lobules in the superficial and deep fibroadipose connective tissue were also recorded [Macchi et al, 2007]. Each region was subdivided into five equal parts and the thickness measured in each part.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Within surgical departments, the need for professionals in human gross anatomy is uncontested (Fasel et al, 2005). In our experience, anatomic and clinical research examines anatomical structures from new perspectives (Macchi et al, 2007b(Macchi et al, ,c, 2008 and can lead to improved surgical practice (Tiengo et al, 2004(Tiengo et al, , 2007Macchi et al, 2005). In our project, the continuity of the diagnostic and therapeutic phases was achieved by the active involvement of residents in the steps involved in donation of body parts.…”
Section: Discussionmentioning
confidence: 95%